2021
DOI: 10.20473/fmi.v57i3.20391
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Population at Risk for Noise Induced Hearing Loss (NIHL) in Adolescent Students

Abstract: Noise-Induced Hearing Loss (NIHL) is a global health problem, often underestimated, and leads to permanent hearing loss. The prevalence of NIHL in adolescents has increased in line with the increasing use of cell phones. This study aimed to determine the prevalence of NIHL and analyze the population at risk (age, gender, and school) in adolescent students. The study design was a cross-sectional study. A total of 510 students consisting of female, n=288 and male, n=222; junior high school, n=203 and senior high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Many studies have reported a pattern of NIHL cases among adolescents [ 22 , 23 , 24 ]. This happens due to the emergence of several factors, such as noise exposure from recreational activities and lifestyle [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported a pattern of NIHL cases among adolescents [ 22 , 23 , 24 ]. This happens due to the emergence of several factors, such as noise exposure from recreational activities and lifestyle [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%